Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Well there are two ways to solve this.
First is by substitutingwe would need to free one of the variable to solve it. It can be one or the other it would result in both ways.
5x - 6y = -113x + 6y = 3
3x + 6y = 3
x=(-6y+3)/3
x= -2y+1
Now we use this and put it in the other of the equations
5(-2y+1) - 6y = -11-10y+5-6y=-11
-16y=-11-5
-16y=-16
y=-16/-16
y=1
Now we use this to find x.
x=-2y+1
x=-2(1)+1
x= -2+1
x=-1
Now that we now our variables we have to check if the are correct.
5x - 6y = -115(-1)-6(1)= -11
-5-6=-11
-11=-11
3x + 6y = 3
3(-1)+6(1)= 3
-3+6=3
3=3
So yeah x=-1 and y= 1
That's a way to solve it there is another way that is by eliminating.
so i this we have to delete a variable in both equations. In thi scase we can take y becuase if we sum the bothe quation 6y and-6y get eliminated.
5x - 6y = -113x + 6y = 3
8x= -8
x= -8/8
x=-1
Now we use this to find the other variable
5(-1) - 6y = -11-5-6y=-11
-6y= -11+5
-6y=-6
y=-6/-6
y= 1
So now we have to check if the are correct.
5x - 6y = -115(-1)-6(1)= -11
-5-6=-11
-11=-11
3x + 6y = 3
3(-1)+6(1)= 3
-3+6=3
3=3
That's that
X= -1
Y= 1
Hope it helped
First is by substitutingwe would need to free one of the variable to solve it. It can be one or the other it would result in both ways.
5x - 6y = -113x + 6y = 3
3x + 6y = 3
x=(-6y+3)/3
x= -2y+1
Now we use this and put it in the other of the equations
5(-2y+1) - 6y = -11-10y+5-6y=-11
-16y=-11-5
-16y=-16
y=-16/-16
y=1
Now we use this to find x.
x=-2y+1
x=-2(1)+1
x= -2+1
x=-1
Now that we now our variables we have to check if the are correct.
5x - 6y = -115(-1)-6(1)= -11
-5-6=-11
-11=-11
3x + 6y = 3
3(-1)+6(1)= 3
-3+6=3
3=3
So yeah x=-1 and y= 1
That's a way to solve it there is another way that is by eliminating.
so i this we have to delete a variable in both equations. In thi scase we can take y becuase if we sum the bothe quation 6y and-6y get eliminated.
5x - 6y = -113x + 6y = 3
8x= -8
x= -8/8
x=-1
Now we use this to find the other variable
5(-1) - 6y = -11-5-6y=-11
-6y= -11+5
-6y=-6
y=-6/-6
y= 1
So now we have to check if the are correct.
5x - 6y = -115(-1)-6(1)= -11
-5-6=-11
-11=-11
3x + 6y = 3
3(-1)+6(1)= 3
-3+6=3
3=3
That's that
X= -1
Y= 1
Hope it helped
5x - 6y = -11
3x + 6y = 3
Rearrange the 2nd equation:
3x + 6y = 3
Subtract 6y to both sides:
3x = -6y + 3
Divide 3 to both sides:
x = -2y + 1
Plug in 2y + 1 for 'x' in the 1st equation:
5x - 6y = -11
5(-2y + 1) - 6y = -11
Distribute 5:
-10y + 5 - 6y = -11
Combine like terms:
-16y + 5 = -11
Subtract 5 to both sides:
-16y = -16
Divide -16 to both sides:
y = 1
Plug this into any of the two equations to find 'x':
3x + 6y = 3
3x + 6(1) = 3
3x + 6 = 3
Subtract 6 to both sides:
3x = -3
Divide 3 to both sides:
x = -1
So our solution is:
(-1, 1)
3x + 6y = 3
Rearrange the 2nd equation:
3x + 6y = 3
Subtract 6y to both sides:
3x = -6y + 3
Divide 3 to both sides:
x = -2y + 1
Plug in 2y + 1 for 'x' in the 1st equation:
5x - 6y = -11
5(-2y + 1) - 6y = -11
Distribute 5:
-10y + 5 - 6y = -11
Combine like terms:
-16y + 5 = -11
Subtract 5 to both sides:
-16y = -16
Divide -16 to both sides:
y = 1
Plug this into any of the two equations to find 'x':
3x + 6y = 3
3x + 6(1) = 3
3x + 6 = 3
Subtract 6 to both sides:
3x = -3
Divide 3 to both sides:
x = -1
So our solution is:
(-1, 1)
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.